2021
DOI: 10.3390/md19020107
|View full text |Cite
|
Sign up to set email alerts
|

Biobased Solvents for Pressurized Liquid Extraction of Nannochloropsis gaditana Omega-3 Lipids

Abstract: To develop greener extraction alternatives for microalgae biomass, ultrasound assisted extraction (UAE) and pressurized liquid extraction (PLE) with different biobased solvents were investigated, demonstrating that both techniques are useful alternatives for algal lipid extraction. Specifically, Nannochloropsis gaditana lipids were extracted by UAE and PLE at different temperatures and extraction times with sustainable solvents like 2-Methyltetrahydrofuran (2-MeTHF) and its mixtures with ethanol and other alco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Previous studies of the research group demonstrated that it was possible to enrich and fractionate neutral and polar lipids using enzymatic pretreatment and pressurized liquid extraction (PLE) from microalgae [1,3,12]. In the present work, the combination of different commercial enzymes, including a wide range of carbohydrases (Viscozyme ® and Celluclast ® ) and protease (Alcalase ® ), were tested in combination with other methods to enhance and optimize polar lipid recovery of N. gaditana dry biomass.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies of the research group demonstrated that it was possible to enrich and fractionate neutral and polar lipids using enzymatic pretreatment and pressurized liquid extraction (PLE) from microalgae [1,3,12]. In the present work, the combination of different commercial enzymes, including a wide range of carbohydrases (Viscozyme ® and Celluclast ® ) and protease (Alcalase ® ), were tested in combination with other methods to enhance and optimize polar lipid recovery of N. gaditana dry biomass.…”
Section: Introductionmentioning
confidence: 99%
“…Among different microalgae that are harvested worldwide, Nannochloropsis gaditana is described to produce a wide range of polar lipids, including omega-3 polyunsaturated fatty acids (PUFAs) and carotenoids such as lutein, which have widely recognized benefits related to human health. Indeed, PUFA produced by microalgae exhibit antioxidant, antibacterial, antiviral, and detoxifying capacities; prevents hypercholesterolemia; improves Foods 2021, 10, 1928 2 of 14 brain function; and is proved to have good immune-stimulatory effects [1,2]. Nannochloropsis gaditana has been described to produce high amounts of lipids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ho et al [31] used a similar strategy to extract the omega-3 EPA but using subcritical water. The use of pressurized liquids has also been reported by several authors [10,32,33]. Moreover, in a recent study, Jiménez Callejón et al, [34] investigated the simultaneous extraction and fractionation of polar lipids by using supercritical and pressurized liquids.…”
Section: Enzyme-based Approaches As Green Alternatives To the Convent...mentioning
confidence: 84%
“…Moreover, the composition of microalgae highly varies among the different species, which make them more versatile. On its own, Nannochloropsis gaditana is described as a microalga able to produce important amounts of lipids, including polar lipids, omega-3 polyunsaturated fatty acids, and carotenoids such as carotenes and xanthophylls, which have benefits for human health widely recognized ( Yen et al, 2013 ; Gong and Bassi, 2016 ; Castejón et al, 2018 ; Castejón and Señoráns, 2019 ; Punia et al, 2019 ; Zhang et al, 2019 ; Castejón and Señoráns, 2020 ; Katiyar and Arora, 2020 ; Señoráns et al, 2020 ; Blanco-Llamero and Señoráns, 2021 ).…”
Section: Introductionmentioning
confidence: 99%